INTERACTION OF FUSARIUM SP. WITH GYRINOPS VERSTEEGII SEEDLING BY MORPHOLOGICAL, ANATOMICAL, AND CHEMICAL OBSERVATION - I Gde Adi Suryawan Wangiyana (SANGKAREANG, 2017)
Studi of interaction between Gyrinops versteegii and Fusarium Sp. could lead advance understanding in agarwood cultivation. The aim of this research is to observe interaction between Fusarium Sp. and Gyrinops versteegii based on morphological, anatomical and chemical observation. Gyrinops versteegii seedling from Lingsar was inoculated by Fusarium sp using grafting method. Morphological observation conducted by observation of chlorosis in leaf and dark colorization in stem. Anatomical observation conducted by observation of seedling stem tissue. Chemical observation conducted by thin layer chromatography. Based on morphological observation, chlorosis of leaf occurred after 14 days inoculation followed by necrosis of leaf at 21 days after inoculation. Penetration of fungal mycelia, fungal conidia and formation of dark coloration on seedling tissue were observed from anatomical observation. Similar spot with similar Rf (0.22) value were observe from seedling sample at 14 days inoculation, 21 days inoculation and also sample of Gyrinops versteegii 6 month after inoculation. All of those spots have similar Rf with standard agarwood oil (Rf = 0.23). Organoleptic test confirmed aromatic odor from seedling at 14 days and 21 day inoculation even though the aromatic odor is not as strong as aromatic odor of Gyrinops versteegii tree at 6 month inoculation. It could be concluded that the inoculation of Fusarium sp. on Gyrinops versteegii resulting: chlorosis and necrosis of leaf, dark colorization of stem, aromatic odor and identical Rf spot of Thin Layer Chromatography.